Monocots of Ludhiana District - Sharma, M. (Indian Forester, 1975)
134 species and 2 varieties belonging to 74 genera included among 18 families or of monocots have been enumerated along with their general distribution and, flowering and fruiting seasons. Grasses with 71 members predominate, followed by 36 sedges.